Expression of courtesy in whatsapp smiley usage among undergraduates - Noorilyana, Hashim (2020)
Fast-growing of Computer Mediated Communication (CMC) usage in Malaysia has risen a concern of courtesy expression including WhatsApp smiley usage. Lack of literature focusing on this particular matter, especially in the Malaysian setting. Moreover, it is strongly recommended to expand and retest Politeness Theory in a non-Western and online context. Previous studies have pointed out the need to address the factors influence and effect courtesy expression in online communication. Thus, this study determines the relationship between emoticons literacy; emotions and expression of courtesy, effect between emoticons literacy; emotions and expression of courtesy, and differences of demographic factors towards an expression of courtesy in WhatsApp smiley usage. This study employed a survey technique and collected data from 377 undergraduate students of Universiti Utara Malaysia. The data were analyzed using descriptive, inferential, and multivariate analysis. Results found that emoticons literacy is the best explains on the greatest effect towards the expression of courtesy in WhatsApp smiley usage. However, the results supported the majority of proposed paths pertaining to the theoretical model. Besides, the study yields an interesting result that inconsistencies with most literature where 'anger' is the most used. Telco service provider, policymakers, universities, and users will be benefited from the results as well as significance to the body of knowledge. Further retesting of Politeness theory is necessary for future studies in a future research context.